KARAKTERISTIK KLINIS PASIEN CHRONIC MYELOID LEUKEMIA DENGAN TERAPI TYROSINE KINASE INHIBITOR DI RUMAH SAKIT UMUM PUSAT SANGLAH - Gabrielle Alexander Kartawan; Ketut Suega; Renny A Rena (Universitas Udayana, 2015)
CLINICAL CHARACTERISTICS OF CHRONIC MYELOID LEUKEMIA PATIENTS WITH TYROSINE KINASE INHIBITOR THERAPY IN SANGLAH HOSPITALChronic Myeloid Leukemia (CML) is the most common type of leukemia in Indonesia. Tyrosine Kinase Inhibitor (TKI) is now the main therapy for CML including imatinib and nilotinib. However, data about clinical characteristics and TKI usage in CML patients are still rare in Indonesia. This study aimed to evaluate clinical characteristics, peripheral blood count, complete hematologic response (CHR) and adverse effects of TKI in CML patients in retrospective cross-sectional study method using medical record of CML patients with TKI therapy in RSUP Sanglah. Twenty nine patients met the criteria. All 29 patients were in chronic phase and 19 of them were males. Median age was 36 years. The most common manifestations were weight loss (100%) and splenomegaly (96%). Imatinib was administered in 21 patients and the rest received nilotinib. Before TKI was administered, median WBC was 118.500/mm3, Hb was 9,5 g/dL, and platelet 338.000/mm3. After 3 months of TKI therapy, median WBC was 14.500/mm3, Hb was 10,9 g/dL, and platelet was 124.400/mm3. Within 3 months of TKI therapy, 13 patients (44,8%) achieved CHR. After TKI therapy, 18 (62,1%) patients got nausea and 16 (55,2%) got myalgia. From hematologic side, 11 (37,9%) got anemia and 10 (34,5%) got trombositopenia. In conclusion, splenomegaly was the most notable manifestations of CML. Achievement of CHR within 3 months in this study was low. The most common non-hematologic adverse effect was nausea while the most common hematologic adverse effect was anemia.